Snow kissed - Thayne, RaeAnne (Canary Street Press, 2025)
Holly's little white lie about having a date to her ex's family wedding backfires -- until Ryan, a handsome newcomer spending Christmas in Shelter Springs, offers to step in. As they team up to give his niece a holiday to remember, their pretend romance starts to feel like the real thing ... and just might lead to the magical Christmas they've both been wishing for.